Measurement of Lumbosacral Angle in Normal Radiographs: A Cross-Sectional Study - Naqvi, Syed Zohaib Gulzar; Ali, Ahmed; Siddiqui, Aslam; Ali, Syed Danish; Qureshi, Mujtaba; Aliuddin, Akram Muhammad (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To determine the value of Lumbosacral angle in normal radiographs. Methodology: The LSA has been measured in lateral lumbosacral spine radiographs taken in the recumbent position in 100 adult individuals visiting Orthopedics Outpatient Department, Baqai Medical University Hospital from 11 – 25 October 2019, with recent onset (less than 2 weeks) non traumatic low back pain without radiculopathy and radiographically vertebral abnormality. Simple randomized probability sampling technique was used. Results: Lumbosacral angle (LSA) of our population is 36± 8 degrees. Mean angle of adult male was 36 degrees, whereas mean angle in adult female was 33. degrees. Conclusion: Present study established that there is no significant difference in LSA between two age groups and sex. Mean Lumbosacral angle in our study group is 36°. This is a milestone cross-sectional study for determining the variations of LSA in our spectrum of patients. In future, author aims to increase the spectrum of population and willing to do a multicenter study to determine LSA value on a larger scale. Keywords: Lordosis, Lumbosacral angle (LSA), Spino pelvic alignment (SPA).